Evaluation of Corporate Social Responsibility Practices: Case Study of Star Energy Geothermal (Wayang Windu) Limited in Pangalengan, Indonesia - Al Furqon, Habib; Rudito, Bambang (Journal of Business and Management, 2016)
Abstract. National development has always been a big issue, moreover ever since the Millennium Declaration back in 2000 at the United Nation summit and attended by 189 countries. Indonesia, with its rich natural and human resource, is having a big advantage to develop. However, the fact in the reality talked different. Even though Indonesia has been able to improve ever since the declaration was made, Indonesia failed to reach the target. One of the government ways to develop the country is by encouraging private sectors to participate in developing the country. One of the ways is by making a certain rule regarding Corporate Social Responsibility that must be done by a company which form has became a liability company. One of the companies who have done this is PT. XYZ. However, a claim from certain local communities and local people that blame the company for the disaster that happened back in the end of 2015 encourage author to evaluate their CSR practice, since the goal of CSR practice is trust and this issue could affect it. This research aims to evaluate the CSR practices of PT. XYZ. Qualitative method, using participant observation approach to several informants would be used to get more information about the issue. The result indicated a gap between the people’s perspective and what the Company wants regarding the CSR practices and some problems were found regarding the system within the practices. SWOT analysis used to know what are the Company’s internal and external factors regarding their CSR practices. Finally, using TOWS analysis, the research would be able to give some strategic recommendations for the Company, which is to empower Marukana UMKM Cooperative to do several things that the Company could not do directly, to make another Community Development program, and to make a periodical and sudden supervision to know how the program is currently running.Keywords: Corporate Social Responsibility, Empowerment, Local Community, PT. XYZ, Sustainability